تحسين تعليم القراءة المكثفة من خلال مواد تعليمية قائمة على الإطار الأوروبي المرجعي المشترك للغات (CEFR) - Irmasani Daulay (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This research addresses the topic of improving intensive reading instruction (in Arabic) through the development of teaching materials aligned with the Common European Framework of Reference for Languages (CEFR). The research focuses on the extent to which the educational content is aligned with the proficiency level of learners, particularly at levels A2-B1, which include skills such as understanding the main idea, inferring implicit meanings, and analyzing the discourse structure of texts. The study adopted the ADDIE research and development (R&D) model, starting with needs analysis and ending with the evaluation of the effectiveness of the teaching materials. The results of expert verification and limited testing showed that CEFR-based teaching materials contribute to a significant improvement in reading proficiency, particularly in terms of reading fluency, accuracy of comprehension, and the ability to interpret contextual meanings. This study confirms that integrating the CEFR not only standardizes teaching criteria, but also makes the learning process more structured, gradual, and aligned with the development of students' ability to understand Arabic texts in depth.